Assessment of Acropora palmata in the Mesoamerican Reef System. - Rosa E Rodríguez-Martínez; Anastazia T Banaszak; Melanie D McField; Aurora U Beltrán-Torres; Lorenzo Álvarez-Filip (PLoS ONE, 2014)
The once-dominant shallow reef-building coral Acropora palmata has suffered drastic geographical declines in the wider Caribbean from a disease epidemic that began in the late 1970s. At present there is a lack of quantitative data to determine whether this species is recovering over large spatial scales. Here, we use quantitative surveys conducted in 107 shallow-water reef sites between 2010 and 2012 to investigate the current distribution and abundance of A. palmata along the Mesoamerican Reef System (MRS). Using historical data we also explored how the distribution and abundance of this species has changed in the northern portion of the MRS between 1985 and 2010-2012. A. palmata was recorded in only a fifth of the surveyed reef sites in 2010-2012. In the majority of these reef sites the presence of A. palmata was patchy and rare. Only one site (Limones reef), in the northernmost portion of the MRS, presented considerably high A. palmata cover (mean: 34.7%, SD: 24.5%). At this site, the size-frequency distribution of A. palmata colonies was skewed towards small colony sizes; 84% of the colonies were healthy, however disease prevalence increased with colony size. A comparison with historical data showed that in the northern portion of the MRS, in 1985, A. palmata occurred in 74% of the 31 surveyed sites and had a mean cover of 7.7% (SD = 9.0), whereas in 2010-2012 this species was recorded in 48% of the sites with a mean cover of 2.9% (SD = 7.5). A. palmata populations along the MRS are failing to recover the distribution and abundance they had prior to the 1980s. Investigating the biological (e.g., population genetics) and environmental conditions (e.g., sources of stress) of the few standing reefs with relatively high A. palmata cover is crucial for the development of informed restoration models for this species.